Differences in Faculty Approaches to Plagiarism Deterrence are an Opportunity for Increased Collaboration in Information Literacy Instruction - Schroeder, Sarah (Evidence Based Library and Information Practice, 2020)
A Review of: Michalak, R., Rysavy, M., Hunt, K., Worden, J., & Smith, B. (2018). Faculty perceptions of plagiarism: Insight for librarians’ information literacy programs. College and Research Libraries, 79(6), 747-767. https://doi.org/10.5860/crl.79.6.747 Abstract Objective – To learn how faculty members define plagiarism and what actions (if any) they are taking in their classes to educate students about plagiarism. Design – Online survey. Setting – A small private college in the Northeastern United States of America. Subjects – A total of 79 full-time and adjunct faculty members in arts and business. Methods – Participants completed an online survey, modified from a survey in The Plagiarism Handbook, in which they provided their definition of plagiarism. They then answered yes/no questions regarding their knowledge levels and methods of plagiarism instruction used in class. The authors collected data on the faculty members’ age, discipline, years of experience, and their status as either adjunct or full-time faculty. After analyzing the results independently, the authors later collaborated to discuss codes and identify clear themes in the list of definitions. Main Results – An analysis of faculty members’ plagiarism definitions determined that most define plagiarism in a way that roughly aligns with the university’s definition, but identified inconsistencies regarding severity, student knowledge, the role of intent, and the necessity of a source attribution when determining what constitutes plagiarism. The themes in their responses clearly illustrate the major differences in approaches to plagiarism. The authors also found that while 87% of respondents reported discussing plagiarism in their classes, they usually did so only “a little” or “a moderate amount.” Furthermore, just over 53% of respondents did not provide their students with materials on plagiarism, though 55% reported including a definition of plagiarism in their course syllabi. Researchers also asked whether or not faculty members had invited a librarian to speak to their class about plagiarism, to which 74% of faculty members responded no. Conclusion – This study suggested that librarians should consider differing perspectives on plagiarism when collaborating with faculty members and that librarian-faculty collaboration on information literacy instruction can help to mitigate the effects of inconsistent practices regarding plagiarism. The study’s authors are integrating their research findings into anti-plagiarism training modules for students at the institution where this study was conducted. Future studies based on this research are planned to further explore the intersections of plagiarism and information literacy.